Peningkatan Literasi dan Numerasi Siswa SDN Karang Manik Melalui Program Kampus Mengajar - Delfi, Iftina; Hidayat, Syafri; Triviana, Fina; Camellia, Camellia (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
Indonesia's PISA results, which are always below the average score and are ranked in the bottom 10, are a strong indicator showing the low literacy and numeracy skills of students, which should be very important for students in strengthening their problem solving abilities, especially in accordance with everyday life. . The state, through the Ministry of Education and Culture, is always creative and innovative to overcome this problem, one of which is by launching the Kampus Mengajar Program which is part of the Merdeka Belajar kampus Merdeka (MBKM) policy. Through this program, students with creative ideas and burning enthusiasm are at the forefront of achieving the above goals. This program is implemented through 3 stages consisting of pre-assignment, assignment and post-assignment. This publication is a publication from students and lecturers of the 5th class of the Kampus Mengajar program with SDN Karang Manik as the placement school. Through the programs that we have designed, the literacy and numeracy skills of SDN Karang Manik students have increased, which can be seen from the comparison of the AKM class pretest and posttest scores conducted at the beginning and at the end of the assignment period which has increased. Even though we only carried out this activity for 1 semester, the work programs that we have designed continue to be carried out by the teachers at the school with the same aim as the aim of holding this Kampus Mengajar program. For us, the Kampus Mengajar program can be used to improve teaching abilities and solve problems that exist in target schools.